Tax policies for inclusive growth in a changing world - O'Reilly, Pierce (OECD Publishing, 2018)
This paper, Tax policies for inclusive growth in a changing world, has been prepared in support of Argentina's G20 Presidency. While this paper is focused on taxation policy, it forms part of a broader contribution that the OECD has made in support of Argentina's G20 presidency. Against a backdrop of increased inequality and persistently low productivity growth, this paper considers the challenges and opportunities confronting policy makers in a rapidly changing world as a result of globalisation, technological change and the changing world of work. The paper focusses on: • The impact of the tax system on the market distribution of income, by supporting employment, skills investments, and labour market formality. • How shifting tax mixes towards growth-friendly taxes can be combined with measures to improve progressivity, particularly through base-broadening and through removing inefficient and regressive tax expenditures. • Ways in which personal income taxes and social transfers can foster inclusive growth by raising the efficiency and equity of labour and capital income tax systems. • How tax policy can foster business dynamism and productivity, including through support for investment and innovation, and can raise efficiency by continuing to combat BEPS. • How tax capacity can be raised, and how tax administration can be strengthened, including through international co-operation The paper provides tax policy advice and recommendations to support governments in their pursuit of tax and transfer policies conducive to inclusive growth, while supporting innovation and increased productivity growth; preserving the revenue-raising capacity of the tax system; and ensuring the sustainability of public spending
Keywords: Taxation